1997
DOI: 10.1577/1548-8640(1997)059<0041:eoslsa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Species, Life Stage, and Water Temperature on the Toxicity of Hydrogen Peroxide to Fish

Abstract: Hydrogen peroxide is a drug of low regulatory priority status that is effective in treating fish and fish eggs infected by fungi. However, only limited information is available to guide fish culturists in administering hydrogen peroxide to diseased fish. Laboratory tests were conducted to determine (1) the sensitivity of brown trout Salmo trutta, lake trout Salvelinus namaycush, fathead minnow Pimephales promelas, walleye Stizostedion vitreum, channel catfish Ictalurus punctatus, and bluegill Lepomis machrochi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 6 publications
1
56
0
10
Order By: Relevance
“…Gaikowski et al (1999) reported that the NOEC for HP in rainbow trout in 60 min exposures administered on Days 1, 3 and 5 at 12°C was 188 mg l −1 in fry and 162 mg l −1 in fingerlings, which is within the range of NOEC values for juvenile rainbow trout reported by Rach et al (1997) at 12°C. Tort et al (2002) reported that the LC 50 of HP to 30 to 60 d old rainbow trout during a single 60 min exposure was approximately 180 mg l −1 at 14°C.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Gaikowski et al (1999) reported that the NOEC for HP in rainbow trout in 60 min exposures administered on Days 1, 3 and 5 at 12°C was 188 mg l −1 in fry and 162 mg l −1 in fingerlings, which is within the range of NOEC values for juvenile rainbow trout reported by Rach et al (1997) at 12°C. Tort et al (2002) reported that the LC 50 of HP to 30 to 60 d old rainbow trout during a single 60 min exposure was approximately 180 mg l −1 at 14°C.…”
Section: Discussionsupporting
confidence: 63%
“…Tort et al (2002) reported that the LC 50 of HP to 30 to 60 d old rainbow trout during a single 60 min exposure was approximately 180 mg l −1 at 14°C. HP oxidises more rapidly with increasing water temperature (Rach et al 1997) and with decreasing pH (Bishop et al 1968), and is therefore more toxic at higher temperatures and lower pH. The dissociation of SPC also releases sodium carbonate, which increases alkalinity and increases and buffers pH (Buchmann et al 2003), stabilising the oxidative rate of HP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We made certain observations in our experiments which may influence the choice of chemical or chemical combination when planning treatments. The toxicity of hydrogen peroxide increases with water temperature (Johnson et al 1993, Bruno & Raynard 1994, Rach et al 1997. Water temperatures in the present study were between 16 and 21°C when we used hydrogen peroxide in combination with formalin.…”
Section: Discussionmentioning
confidence: 64%
“…We also used Per Aqua and Desirox, which both contain 20% hydrogen peroxide. The hydrogen peroxide doses we used followed the recommended treatment range from 50 to 250 ppm for exposures up to 60 min (Rach et al 1997). In the Per Aqua (40 ppm) and hydrogen peroxideformalin (both 100 ppm) tanks, mortality increased to a moderate level (4 to 13%) during the experiments at Farm A in both years, whereas when Desirox (10 ppm) was used in combination with formalin (100 ppm) mortality was below 2% and the parasite burden was the lowest of the 3 treatments used at Farm A in 2002.…”
Section: Discussionmentioning
confidence: 99%